New insights into the neuroprotective and beta-secretase1 inhibitor profiles of tirandamycin B isolated from a newly found Streptomyces composti sp. nov. - Thitikorn Duangupama; Jaturong Pratuangdejkul; Sumet Chongruchiroj; Pattama Pittayakhajonwut; Chakapong Intaraudom; Sarin Tadtong; Patcharawee Nunthanavanit; Weerasak Samee; Ya-Wen He; Somboon Tanasupawat; Chitti Thawai (My University, 2023)
Tirandamycin (TAM B) is a tetramic acid antibiotic discovered to be active on a screen designed to find compounds with neuroprotective activity. The producing strain, SBST2-5T, is an actinobacterium that was isolated from wastewater treatment bio-sludge compost collected from Suphanburi province, Thailand. Taxonomic characterization based on a polyphasic approach indicates that strain SBST2-5T is a member of the genus Streptomyces and shows low average nucleotide identity (ANI) (81.7%), average amino-acid identity (AAI) (78.5%), and digital DNA-DNA hybridization (dDDH) (25.9%) values to its closest relative, Streptomyces thermoviolaceus NBRC 13905T, values that are significantly below the suggested cut-off values for the species delineation, indicating that strain SBST2-5T could be considered to represent a novel species of the genus Streptomyces. The analysis of secondary metabolites biosynthetic gene clusters (smBGCs) in its genome and chemical investigation led to the isolation of TAM B. Interestingly, TAM B at 20 µg/mL displayed a suppressive effect on beta-secretase 1 (BACE1) with 68.69 ± 8.84% inhibition. Molecular docking simulation reveals the interaction mechanism between TAM B and BACE1 that TAM B was buried in the pocket of BACE-1 by interacting with amino acids Thr231, Asp 228, Gln73, Lys 107 via hydrogen bond and Leu30, Tyr71, Phe108, Ile118 via hydrophobic interaction, indicating that TAM B represents a potential active BACE1 inhibitor. Moreover, TAM B can protect the neuron cells significantly (% neuron viability = 83.10 ± 9.83% and 112.72 ± 6.83%) from oxidative stress induced by serum deprivation and Aβ1-42 administration models at 1 ng/mL, respectively, without neurotoxicity on murine P19-derived neuron cells nor cytotoxicity against Vero cells. This study was reportedly the first study to show the neuroprotective and BACE1 inhibitory activities of TAM B.
Keywords: Docking (animal); Strain (injury); Microbial Natural Products and Biosynthesis